Refusal Strategies of Thai and American Instructors at Chiang Mai University - Kanokwan Kantakorn (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This study aims to compare and contrast refusal strategies employed by Thai and American instructors working at Chiang Mai University and to investigate the effects of the social status of interlocutors on refusal strategies employed by both groups of instructors. The data was collected by means of a Discourse Completion Test (DCT) completed by 15 Thai instructors and 15 American instructors. The DCT included situations of requests and suggestions for the participants to indicate how they would refuse. In addition, this study investigates whether or not the participants employ the refusal strategies that correspond to those in Brown and Levinson’s Politeness Theory. The results indicate that both groups of participants performed speech acts of refusal in a similar way since members of both groups preferred indirect strategies to direct strategies. The factor of social status did not appear to have much effect on refusal strategies for either type of speech acts investigated: requests and suggestions. Both Thai and American instructors employed ‘explanation/reason/excuse’ as the main strategy when refusing interlocutors of higher, equal, and lower status. However, it was observed that the content of the ‘explanation/reason/excuse’ of each group was different when refusing a superior’s request to work in a team with a person they dislike. American instructors mostly referred to an unpleasant work relationship and personal differences with the person in question, while Thai instructors gave as reasons their own lack of appropriate skills for the task and their availability. The findings were also analyzed under Brown and Levinson’s Politeness Theory and it was found that both groups of participants employed four main politeness strategies: 1) bold on record, 2) positive politeness, 3) negative politeness, and 4) off-record, to maintain the hearer’s positive face.